2020
DOI: 10.3389/fimmu.2020.00700
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Composition and Its Impact on the Development of Allergic Diseases

Abstract: Allergic diseases, such as food allergy (FA), atopic dermatitis (AD), and asthma, are heterogeneous inflammatory immune-mediated disorders that currently constitute a public health issue in many developed countries worldwide. The significant increase in the prevalence of allergic diseases reported over the last few years has closely paralleled substantial environmental changes both on a macro and micro scale, which have led to reduced microbial exposure in early life and perturbation of the human microbiome co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 96 publications
0
90
0
1
Order By: Relevance
“…A recent Cochrane Review 15 included 39 randomized controlled trials with 2599 randomized participants of either gender, aged from the first year of life through to 55 years (only six studies assessed adults) 1 . The probiotics included were bacteria of the Lactobacillus and Bifidobacteria species taken alone or in combination with other probiotics for a period ranging from four weeks up to six months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Cochrane Review 15 included 39 randomized controlled trials with 2599 randomized participants of either gender, aged from the first year of life through to 55 years (only six studies assessed adults) 1 . The probiotics included were bacteria of the Lactobacillus and Bifidobacteria species taken alone or in combination with other probiotics for a period ranging from four weeks up to six months.…”
Section: Resultsmentioning
confidence: 99%
“…The early microbiota is proposed to have a role in the pathogenesis of atopic dermatitis (AD) 1 . Therefore, it has been argued that modulating the host's gut microbiota could be an approach for preventing and/or treating allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Characterizing the constituents of the human gastrointestinal, skin, and airway microbiota as well as microbial peptides and metabolites that influence host immunity and immune response to allergens in food allergy, atopic dermatitis, and asthma is the focus of ongoing research. 60,61 Composition of the microbiome has been found to vary even within an organ system, such as the skin, with variations in the microbiome observed between the scalp, arm, and axilla. 62 Advances in our understanding of host-microbe interactions have been made possible by 16S rRNA sequencing, which permits precise identification and quantification of bacteria.…”
Section: Microbiomementioning
confidence: 99%
“…Given the central role of the first 1,000 days of life for the development of the immune system, numerous studies have investigated the role of intrauterine exposures in the pathogenesis of allergic diseases (11). Recent evidence supports the hypothesis that colonization by a healthy gut microbiome during early infancy can affect the immune system development and the predisposition to immune-mediated diseases later in life, including asthma (12,13). It has been shown that the maternal diet during pregnancy could influence the composition of the gut microbiome and the immune system development of the neonate, and therefore potentially affect the predisposition to asthma and allergies in childhood (14,15).…”
Section: Maternal Diet During Pregnancymentioning
confidence: 80%